PENGARUH PENGALAMAN KERJA, PELATIHAN KERJA, DAN KODE ETIK TERHADAP KINERJA AUDITOR - Deasusanti, I Gusti Ayu Ketut Berliana Deasusanti; Suhaedi, Wirawan; Waskito, Iman (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2023)
The study aims to test and determine the effect Work Experience, Work Training, Code Of Ethics on Auditor Performance. This study uses a quantitative approach. The populations in this study are all auditors who work in office West Lombok District Inspecorate and Mataram City Inspectorate. The sampling technique used is a saturated sample where all members are used as samples, with a total sample of 46 auditors. Data collection was carried out by giving questionnaires directly to all sample, and 44 questionnaires wer returned. Data analysis techniques in this study using Partial Last Square (PLS). The results of this study indicate that Work Experience, Work Training, Code of Ethics have a positive and significant effect on auditor performance.